Implementation of Learning Communication System: A Case Study on Buddhist Religious Teachers in State Elementary School - Edi Sumarwan; Tejo Ismoyo; Susanto; Juni Suryanadi; Janita Dewi (LPPM STIAB JINARAKKHITA LAMPUNG, 2023)
This study aims to analyze and describe the implementation of online learning of Buddhist religious education teachers at State Elementary School 01 Sripendowo. This research uses a case study method with a qualitative approach. Data were obtained using observation, interview, and documentation methods. Furthermore, the data obtained were analyzed using the Miles and Huberman model. The existence of learning problems during the co-19 pandemic made researchers interested in conducting research related to the online learning communication system. The results showed that teachers used communication elements following the model given by Laswel. In addition, the findings also explain that the teacher takes seven practical strategic steps in carrying out the online learning communication system. This study also found five common barriers experienced by teachers during the implementation of online learning.